Formação de professores em um curso de aperfeiçoamento para professores de língua inglesa em contexto virtual: as relações estabelecidas no fórum de discussão - Arruda, Belia Fantina Bonini Pinto de (2012)
This research aims to understand form a critical point of view, which is, focused on understanding the issues raised in discussion with a view to creating zpds for questioning and collaborative production of new meanings and contexts created for learning and development in a virtual context of an English course in English language training for teachers - Teachers' Links. The theoretical-methodological research is based on, Bredo and Feinberg (1982) to analyze and understand, critically, how e context for learning, are established in the Discussion Forums, on a virtual environment of a specialization course for English language teachers Teachers Links, For the development of data analysis, I use the categories of collaboration and conflict, according to Oliveira and Magalhães (2011), the category of ZPD according to Magalhães (2002, 2009) and Newman and Holzman (1993/2002) and the category of senses and meanings, (Liberali, 2009); (Magalhães, 1996, 2004, 2007, 2010). The categories of analysis to check the engagement of participants in the discussions in the forums are the thematic and lexical choices, the types of questions ( Brooks field-Preskill (2005) among the students and teachertutor to analyze how language is organized in the messages posted in the forums, the types of placement of students, teachers and tutors (if one explains the purpose of the assignments, how to act; or if he simply ignores the speech of the other); and if their assignments are completed by the participants or not. The data were selected from the database of the Teachers' Links, more precisely the Discussion Forums. The results of this study show that in the virtual context, in this case, Discussion Forums, the proposed assignments in order to create relationships that allow spaces for learning and development should be reviewed and thought the papers, the division of labor and rules among the participating subjects, i.e., the teacher-tutor and students, for it is possible to create these spaces